The evaluation of usability of i-Rehlah prototype based on experts' consensus using fuzzy delphi analysis / Mohammad Imran Ahmad ... [et al.] - Ahmad, Mohammad Imran; Adnan, Ahmad Syukri; Mansor, Naqibah; Jaffar, Mohammad Najib (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
To verify the product's usefulness, each application must go through a testing or evaluation phase. Usability evaluation is described as a test performed on a real user to assess how easy it is to use an application. In this study, the respondents must use the developed prototype and give an evaluation of the questionnaire provided in order to determine the usability of the i-Rehlah prototype. Since the evaluation of usability could not be applied to Arab tourists as the main respondents, the authors decided to appoint professionals in academia, industry, and government as respondents. For the initial phase of construction for the real application, the choice of this technique and a target group of experts is deemed appropriate. This study aimed to obtain experts' consensus on the elements of i-Rehlah prototype application. The main focus of this study is to assess the efficacy of the i-Rehlah prototype, which aims to make it easier for travelers, particularly Arab tourists, to travel in Selangor. This study was used the Fuzzy Delphi Method (FDM) to achieve the result. This questionnaire contains three main domains with total 21 items and was distributed to 10 respondents. The criteria and characteristics of the experts who are the subject of this study are very much in line with the context of the study because it involves experts in the fields of academia, industry and government. The results show that two of the three domains got expert agreement, namely the information and interface domains. Meanwhile, for the interactive domains, four of the eight items stated were rejected by the experts due to a lack of fuzzy score requirements. As a result, this prototype is only examined by professionals who are knowledgeable and qualified to do so before it is released.